2017
DOI: 10.1108/aeat-09-2014-0137
|View full text |Cite
|
Sign up to set email alerts
|

Experimental experience of cold starting a spark ignition UAV engine using low volatility fuel

Abstract: Purpose -The purpose of this paper is to present results of practical experience of cold starting a gasoline engine on low volatility fuel suitable for Unmanned Air-Vehicle (UAV) deployment. Design/methodology/approach -Experimental research and development via dynamometer testing of systems capable of achieving cold start of a spark ignition UAV engine on kerosene JET A-1 fuel. Findings -Repeatable cold starts have been satisfactorily achieved at ambient temperatures of 5°C. The approximate threshold for warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…If the fuel film compensation is too rich, the mass ratio of fuel to air will be quite high, which will result in poor fuel economy and increased emissions (Kousoulidou et al , 2013; Cárdenas et al , 2015). Meanwhile, it is an effective method to preheat the engine cylinders with glow plugs (Hooper, 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…If the fuel film compensation is too rich, the mass ratio of fuel to air will be quite high, which will result in poor fuel economy and increased emissions (Kousoulidou et al , 2013; Cárdenas et al , 2015). Meanwhile, it is an effective method to preheat the engine cylinders with glow plugs (Hooper, 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the manufacturing cost of kerosene is comparatively low considering its widespread application in the current aviation industry [13]. Aviation kerosene and light diesel can also temporarily serve as the fuel supply for land vehicles, showing its good universality [15,16]. Based on the above reasons, the transition from regular gasoline to heavy fuel can be observed in the research field of power fuel for small and medium-sized UAVs [17].…”
Section: Introductionmentioning
confidence: 99%
“…This has been an area of active research, and several companies have introduced products onto the market. Practical application has confirmed that a gasoline piston engine can work well while applying kerosene-based fuel as a raw material (Li and Wei, 2012;Hooper and Al, 2012;Hooper, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on stratified charge technology, such engines can burn a variety of fuels including gasoline, kerosene and diesel, and start up smoothly without auxiliary measures required at low temperature. The stepped piston engine designed and developed by Bernard Hooper Engineering, Ltd was shown to have the ability to work well with kerosene-based fuel (Hooper, 2001(Hooper, , 2017. Two-stroke aircraft engines operated at 20 to 50 hp were converted to run on JP8 fuel using the Sonex Combustion System developed by Sonex Research, Inc.…”
Section: Introductionmentioning
confidence: 99%